DNA restriction fragment length polymorphism analysis of Mycobacterium tuberculosis isolates from HIV-seropositive and HIV-seronegative patients in Kampala, Uganda - Asiimwe, Benon B.; Joloba, Moses L.; Katabazi, Fred A.; Kallenius, Gunilla (BMC infectious diseases, 2009)
The identification and differentiation of strains of Mycobacterium tuberculosis by DNA fingerprinting has provided a better understanding of the epidemiology and tracing the transmission of tuberculosis. We set out to determine if there was a relationship between the risk of belonging to a group of tuberculosis patients with identical mycobacterial DNA fingerprint patterns and the HIV sero-status of the individuals in a high TB incidence peri-urban setting of Kampala, Uganda. One hundred eighty three isolates of Mycobacterium tuberculosis from 80 HIV seropositive and 103 HIV seronegative patients were fingerprinted by standard IS6110-RFLP. Using the BioNumerics software, strains were considered to be clustered if at least one other patient had an isolate with identical RFLP pattern. One hundred and eighteen different fingerprint patterns were obtained from the 183 isolates. There were 34 clusters containing 54% (99/183) of the patients (average cluster size of 2.9), and a majority (96.2%) of the strains possessed a high copy number (≥ 5 copies) of the IS6110 element. When strains with <5 bands were excluded from the analysis, 50.3% (92/183) were clustered, and there was no difference in the level of diversity of DNA fingerprints observed in the two sero-groups (adjusted odds ratio [aOR] 0.85, 95%CI 0.46–1.56, P = 0.615), patients aged <40 years (aOR 0.53, 95%CI 0.25–1.12, P = 0.100), and sex (aOR 1.12, 95%CI 0.60–2.06, P = 0.715). The sample showed evidence of a high prevalence of recent transmission with a high average cluster size, but infection with an isolate with a fingerprint found to be part of a cluster was not associated with any demographic or clinical characteristics, including HIV status.